KEBIJAKAN PEMERINTAH KOTA PEKANBARU MENGENAI PERTUMBUHAN PENDUDUK TAHUN 2008-2012 - Iin Ismawati; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
With the increasing development activities led to increased activity in all fields of population, which in turn has also increased the demands and needs of the community towards the provision of urban facilities and utilities and other necessities. The number of inhabitants in an area affected by the level of fertility, mortality and migration. Variable fertility and mortality at this time does not significantly affect the growth of a population especially in urban areas. In urban areas migrasilah dominant variable in the population increase. Due to the growth and increasing population, the of Pekanbaru city increasingly crowded. As for the impact of this population growth is the increasing unemployment, homelessness and lead to poverty, traffic congestion, and crime rates.This research was conducted in the Department of Population and Civil Registration Pekanbaru. The theory used is related to Public Policy. Methods This study is a qualitative study, while data collection techniques are observation, interviews, and documentation. While data analysis is done descriptively. This study examines the government's policy of Pekanbaru in suppressing population growth rate, government policies in reducing the speed of Pekanbaru city population growth rate is not maximized, and area constraints Regulation Number 5 of 2008 concerning the administration of the population in the of Pekanbaru city. Pekanbaru city government policy regarding the speed of population growth to suppress the population growth rate is based on Regional Regulation Number 5 of 2008 Pekanbaru administration on population, which contained three indicators used by the government to reduce the rate of population growth in the of Pekanbaru city the guidance, supervision, and control.Key words : Public Policy, Regulation, Population Growth